EFFECT OF ACU-TENS ON SNORING - MANDEEP BEDI,; JASOBANTA SETHI, (International Journal of Pharma and Bio Sciences, 2015)
Improving sleep disturbances in patients with snoring are of primary importance. The purpose of this study was to examine the effect of TENS on acupoints (HT4, HT5, HT6) in patients with snoring. 60 subjects with 18-65 yrs of age, who had complains of snoring were assigned to 2 groups; Experimental group (treated with TENS, Diet and Deep Breathing Exercise) and Control group (treated with Placebo TENS, Diet and Deep Breathing Exercise) and were given treatment for 15 days. Pre and post test readings of snoring by using the Epworth Sleepiness Scale, Berlin Questionnaire of patients in both the groups were taken before and after intervention. ignificant difference was found within experimental group and between the groups in reduction of snoring.